A facile approach assembled magnetic CoFe2O4/AgBr composite for dye degradation under visible light. Issue 2 (April 2017) - Li, Zhenlu; Ai, Jingzhe; Ge, Ming
Graphical abstract: Highlights: Magnetic CoFe2 O4 /AgBr composite was firstly synthesized by a facile method. CoFe2 O4 /AgBr composite exhibited high photocatalytic activity under visible light. CoFe2 O4 /AgBr composite was separated easily and showed long reusable life. The photocatalytic mechanism of the CoFe2 O4 /AgBr was proposed. Abstract: A simple precipitation–deposition method for the synthesis of the magnetic CoFe2 O4 /AgBr composite has been developed to improve the photocatalytic activity of AgBr, and also to reduce the high cost of AgBr. The as-synthesized samples were characterized via XRD, XPS, FE-SEM, UV–vis DRS and PL. The 20%CoFe2 O4 /AgBr composite exhibited a higher photocatalytic performance under visible light for MO degradation compared with pure AgBr. The photodegradation rate of MO over 20%CoFe2 O4 /AgBr catalyst decreased with increasing the initial concentration and pH of MO solution. The photocatalytic dye degradation performance by 20%CoFe2 O4 /AgBr occurred in the order of RhB > MO > MB. The composite can be quickly separated from the solution by an external magnetic field, and three consecutive regeneration cycles demonstrated that the photocatalytic activity of 20%CoFe2 O4 /AgBr composite is stable. The trapping experiments indicated that the superoxide radicals were the main reactive oxygen species in CoFe2 O4 /AgBr system. The photocatalytic activity enhancement of CoFe2 O4 /AgBr composite could be ascribed to the efficient separation of electron-hole pairs.